Multiple Objective Budgeting Models: A Simulation. - Lin, W. Thomas (The Accounting Review, 1978)
Abstract ABSTRACT: This article examines the effects of alternative planning models and accounting variance analysis techniques on a firm's profit and sales performance. Two multiple objective product-mix models, a satisficing goal programming model and an optimizing multiple objective linear programming model, are developed within an uncertain demand situation. Two accounting control systems, a traditional standard cost variance analysis and an ex post variance analysis, are also investigated. A computer simulation experiment is conducted, and F-tests, as well as a multiple-ranking procedure, are used to analyze the simulated results. The simulation results show that profit and sales under multiple objective linear programming are higher than those under goal programming. When comparing ex post variance analysis with traditional variance analysis, the former results in hgher sales, but there is no significant difference in profits. Possible reasons for this is explored and a sensitivity analysis was conducted.